Design of a 20 wp solar panel DC power monitoring system based on the internet of things - Tianur; Hidayat Ramadhan Putra; Ramadhani Amellia (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
The role of solar panels is to transform solar energy into electrical energy. The process of monitoring solar panel output is still done in the traditional manner, which takes a lot of time and produces less reliable data. In order to solve this issue, a system that can track data produced by solar panels in real time and remotely via an application has been developed. With the help of the Internet of Things (IoT), this monitoring system, which makes use of a 20 WP solar panel, will show data in the form of readings of light intensity, voltage, current, and applications made with MIT App Inventor that use real-time databases on Firebase and the ESP32, and that are powered by DC power. Several tests were run on sending data to customers in this study while looking for the delay value. The solar panel's output voltage is measured against the greatest value for sunshine intensity, and output is also measured with and without a 12V DC lamp load on the battery. With an average time of 18.01 seconds, the data monitoring results were obtained to inform consumers. The highest value occurred at 12.00 WIB with an intensity of 54,588 lux and a solar panel output voltage of 20.01 volts. When the battery's output is measured without a load, it averages 12.56 volts, 0.02 amps, and 0.2 watts; when the battery's output is measured with a 12 volts direct current light load, it averages 11.98 volts, 0.40 amps, and 4.8 watts. Real-time monitoring of solar panel dc power is substantially facilitated by this monitoring method